Home Environmental factors with the Incidence of ISPA in Toddlers Indonesia: Literature Review - Inggita Raiesa Rahmi; Rosa Pini Septiani S; Khairul Rasyid (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Background: ARI or acute respiratory infections can occur in the upper and lower respiratory tract. Toddlers are at risk of ARI due to indoor air pollution. Indonesia has the highest mortality rate of children under 5 years old due to ARI caused by several unqualified environmental factors such as ventilation area, occupancy density, air humidity, and lighting of toddlers' homes that do not meet the requirements of healthy homes. This literature review aims to analyse the association between home environmental factors and the incidence of ARI in children under five years of age in Indonesia. Method: Using the literature review method by reviewing scientific articles published in the Google Scholar, Researchgate, Sciencedirect and PubMed databases using the search keywords OR factors using boolean operators AND ARI in toddlers OR Accute Respisitory Infections under five years. The study was conducted from June to August 2024 in Indonesia. Result: 12 articles were found that met the inclusion criteria of the study. of the 12 articles reviewed showed that air temperature, air humidity, lighting intensity, ventilation area, residential density in the house, use of fuel for cooking, the presence of family members who smoke in the house are associated with the incidence of ARI in Indonesia. Conclusion: The most dominant factor associated is the presence of family members who smoke. Some other factors that are interconnected are the availability of adequate ventilation with air humidity in the house. Many of the toddlers affected by ARI live in homes that do not have adequate ventilation so that the humidity in the house becomes high and creates an environment that supports the growth of pathogenic germs that can increase the risk of ARI in toddlers.